Laboratory for Economic Sociology Research’s Textual Study Seminar Series «Economic and Sociological Concepts of Competition», SU HSE, Moscow (Russia), 20 December 2010 - Максим Евгеньевич Маркин (Journal of Economic Sociology, 2011)
Detailed description in the text